Combustion-synthesized Ru-Al2O3 composites as anode catalyst layer of a solid oxide fuel cell operating on methane - Wang, W.; Ran, R.; Shao, Zongping (2011)
Ru-Al2O3 composites with varied Ru contents were synthesized by a glycine-nitrate combustion technique. Their potential application as anode catalyst functional layer of a solid-oxide fuel cell operating on methane fuel was investigated. Catalytic tests demonstrated the 3-7 wt.% Ru-Al2O3 composites had high catalytic activity for methane partial oxidation and CO2/H2O reforming reactions, while 1 wt.% Ru-Al2O3 had insufficient activity. The 3 wt.% Ru-Al2O3 catalyst also showed excellent operation stability and good thermal-mechanical compatibility with Ni-YSZ anode. H 2-TPR and TEM results indicated there was strong interaction between RuOx and Al2O3 in the as-synthesized catalysts, which may account for the good catalytic stability of 3 wt.% Ru-Al 2O3 catalyst. O2-TPO results demonstrated Ru-Al2O3 also had excellent coking resistance. Furthermore, the carbon deposited over Ru-Al2O3 had lower graphitization degree than that deposited over Ni-Al2O3, suggesting the easier elimination of potential carbon deposited over the Ru-Al2O3 catalysts. A cell with 3 wt.% Ru-Al 2O3 catalyst functional layer was prepared, wh-ich delivered peak power densities of 1006, 952 and 929 mW cm-2 at 850 °C, operating on methane-O2, methane-H2O and methane-CO2 gas mixtures, respectively, comparable to that operating on hydrogen fuel. It highly promised 3 wt.% Ru-Al2O3 as a coking resistant catalyst layer for solid-oxide fuel cells. © 2010 Professor T. Nejat Veziroglu. Published by Elsevier Ltd. All rights reserved.